Enhancement of transmission range assignment for clustered wireless sensor networks - Salamah, Muhammed; Hussein, Ahmed Ali (Academy and Industry Research Collaboration Center (AIRCC), 2016)
Transmitter range assignment in clustered wireless networks is the bottleneck of the balance between energy conservation and the connectivity to deliver data to the sink or gateway node. The aim of this research is to optimize the energy consumption through reducing the transmission ranges of the nodes, while maintaining high probability to have end-to-end connectivity to the network's data sink. We modified the approach given in [1] to achieve more than 25% power saving through reducing cluster head (CH) transmission range of the backbone nodes in a multihop wireless sensor network with ensuring at least 95% end-to-end connectivity probability. © 2016, Academy and Industry Research Collaboration Center (AIRCC).
Keywords: Clustering; connectivity; Transmission range; Wireless ad hoc networks; Wireless sensor networks